The Influence of Selection, Talent Management, and Employee Placement on Employee Performance and Its Impact on the Performance of Pt Pupuk Iskandar Muda Aceh (International Journal of Scientific Research and Management (IJSRM), 2024)
This research examines the role of employee performance in mediating the selection, talent management, and placement influence on the performance of PT Pupuk Iskandar Muda Aceh. This research has the same population and sample size, namely 305 because it uses proportionate stratified random sampling techniques and is analyzed through SEM AMOS. The research results prove that selection, talent management, placement, employee performance, and organizational performance have gone well; selection, talent management, and placement have a significant influence and positive function on increasing employee and company performance; and employee performance has a positive and significant influence on PT Pupuk Iskandar Muda Aceh’s performance. Employee performance is significant and has a positive function in mediating the position of talent selection and management, as well as placement, and its mediating influence is partial.